Development of Learning Everywhere Class (LEKAS) Platform for Economic Education - Megasari, Rizza; Haryono, Agung; Putri, Rizky Dwi; Rokhmani, Lisa; Inayati, Ro’ufah; Handayani, Sri; Annisya’, Annisya’ (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The main objective of this research is to develop an Android-based mobile learning platform for economic education students so that they can study anywhere and anytime. Following the current trend, learning must be flexible in accordance with learning styles that tend to lead to online learning. Students will be more comfortable studying with their smartphones anywhere than having to carry books everywhere. This platform consists of several features, namely lecture material, evaluation results and progress of reading material in the form of PDF and video embedding. The design development in this study uses the ADDIE model, which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. This product was tested on 60 students of economic education class 2019 in introduction of macroeconomics courses. The final product of this research is an Android-based mobile learning platform with the title LEKAS (Learning Everywhere Class). The results of the evaluation of this product are that there is still a need for improvements in the ease of access to various types of android. The advantage is that students can immediately learn and find out the extent of understanding by taking tests after studying the material that has been shared. Through this platform students can study material and evaluate the material they read anywhere and anytime. The convenience provided on this platform will be able to increase the effectiveness and efficiency of learning in economic education.